Impact Analysis of SMEs Sector in Economic Development of Pakistan: A Case of Sindh - Syed, Anwar Ali Shah G; Ahmadani, Muhammad Muneer; Shaikh, Naveed; Shaikh, Faiz Muhammad (Journal of Asian Business Strategy, 2012)
This study examines the role of SMEs for the economic development of Pakistan. A comprehensive international literature study was undertaken. The data were collected from the 100 owners/managers and 200 employees of the SMEs of textile industry by using five point Likert scale through the survey of 50 small and medium-sized textile units. The data were analyzed by using descriptive statistics, paired sample t-test and Pearson’s product moment correlation analysis. The results of this study revealed that SMEs are playing a positive and significant role for the economic progress of Pakistan, fundamental role in foreign exchange earnings and GDP of Pakistan. The present study further suggested that SMEs are also providing job opportunities in the country and have a major contribution in export sub-sector of Pakistan.